Tristable behaviour of cross-shaped unsymmetric fibre-reinforced laminates with concave–convex boundaries. (15th December 2020) - Li, Yang; Zhang, Zheng; Yu, Xiaochen; Chai, Hao; Lu, Congda; Wu, Helong; Wu, Huaping; Jiang, Shaofei
Highlights: A cross-shaped unsymmetric laminates has three stable configurations. The width will change the concave-convex boundary of the laminates. The sidelength and width determine whether the laminate has multistability. Abstract: This paper presents cross-shaped unsymmetric fibre-reinforced cross-ply laminates with concave–convex boundaries, which have three stable configurations. The third stable equilibrium configuration is a transition state which occurs in the snap process from the first to second equilibrium configurations. The snap processes, including the first–third–second and second–third–first, between the different stable equilibrium configurations of tristable cross-shaped unsymmetric laminates were investigated by experimental and numerical methods, and the parameters that characterise the tristable performance of the laminates, including the principal curvature, snap load, and displacement, were measured. The principal curvatures in different stable configurations were determined with analytical, experimental, and numerical methods, and the load–displacement curves and buckling phenomena in the snapping process were successfully recorded. Moreover, the influences of the reinforcement material, thickness of the single layer, and geometric parameters on the tristable performance of the cross-shaped unsymmetric fibre-reinforced cross-ply laminates were discussed. According to the results, the analytical, experimental, and numerical results agree well.